Adaptation of the assessment processes and its impact on learners: during and post-Covid19 situation in Bangladesh - Tabassum, Rezuana (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2022.